Researching the factors and benefits in increasing the use of AI color cosmetics - Balqiah, Ezni; Trianesti, Ginsi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The recent developments in smartphone technology and social media platforms have led to a growth in the popularity of artificial intelligence (AI) color cosmetics as an innovative solution to promote branded color cosmetics and improve consumer decision- making making, especially as a trial purpose. The objective of this research is to examine and analyze the factors that will increase and also the benefits resulting from AI Color Cosmetic Usage. The survey of research design was used to test the 8 research hypotheses. This research is using purposive sampling technique and data collected from 349 respondents. Furthermore, the research model was analyzed using PLS-SEM. The results of data processing show all significant hypotheses. It is proven that Body Esteem, Price Sensitivity, Social Media Addiction have positively influence on AI Color Cosmetic Usage, which in turn also positively inflluence Trust in Artificial Intelligence, eWOM Engagement, Consumer Satisfaction, Purchase Intention. The findings of this research is add to the empirical development of the literature on AI Color Cosmetic Usage and have managerial implications for promotion managers working for cosmetic brand as well as AI color cosmetics application developers who are attempting to advertise and reach a broader market segment.